Sistem Informasi Sewa Lapangan Harahap Futsal Berbasis Android (Studi Kasus : Harahap Futsal Rantauprapat) - Pepi Dian Fauji; Syaiful Zuhri Harahap; Marnis Nasution (Universitas Labuhanbatu, 2022)
Futsal is one of the sports that are popular with the community. In addition to a good futsal court, a good field rental system is also a factor in consideration for tenants choosing futsal court rentals. Futsal field rental system that is still manual will make the length of the process of recording and searching for information. as well as a booking system that has to come face to face and come directly to a certain place will take a lot of time to do it. Nowadays cell phones have become an important part.Android is the operating system most used by smartphone lovers today. The futsal field rentalapplication was built using eclipse and using Mysql database storage media. Based on the trial results, it is known that the Android-based futsal field rental application can be used as a futsal field rental media. With the application of this field rental aims to simplify the rental application are data collection activities and user interface design, with eclipse support software for making applications. the result obtained from the field rental application simplify the field booking process.